The use of household biomass and the incidence of acute respiratory infection (ARI) in toddlers in Lampung Regency 2020 - Cahyani, Evirusi; Ismail, Djauhar (Universitas Gadjah Mada, 2022)
Purpose: Acute Respiratory Infection (ARI) is a significant cause of illness and mortality in children under five, with those under two years being the most vulnerable. The World Health Organization (WHO) estimated in 2017 that ARI contributed to up to 3 million deaths worldwide, particularly in low-income countries. In Indonesia, the 2018 Basic Health Research reported an ARI prevalence of 12.80%, while Lampung Province recorded a rate of 11.3%. In Central Lampung District, the prevalence of ARI with acute nasopharyngitis was 19.70%. One of the primary risk factors for ARI in toddlers is indoor air pollution, often linked to household cooking fuel. Biomass fuel combustion generates smoke and pollutants that can lead to respiratory infections. This study analyzed the association between household biomass fuel use and the incidence of ARI in toddlers in the Seputih Surabaya Health Center working area, Central Lampung, in 2020. Methods: This was an observational analytic study using a cross-sectional design. One hundred four participants from the Seputih Surabaya Health Center area were included. Univariable analysis was performed using frequency distribution tables, bivariable analysis utilized the Chi-Square test, and multivariable analysis applied logistic regression. Results: The findings indicated a significant relationship between household biomass fuel use and toddler's ARI incidence (p = 0.000). Multivariate logistic regression analysis showed that biomass fuel use contributed 25% to the risk of ARI in toddlers. Conclusion: Several factors, including biomass fuel use, maternal age, maternal education, toddler age, exclusive breastfeeding, exposure to cigarette smoke, and socio-economic status, were found to be associated with ARI incidence in toddlers.